Синдром множинної ендокринної неоплазії 2-го типу - Бойко, Н. І.; Хом’як, В. В.; Павловський, М. П.; Довгань, Ю. П.; Гавриш, Я. І.; Кемінь, Р. В. (Clinical Endocrinology and Endocrine Surgery, 2011)
Multiple endocrine neoplasia (MEN) syndrome – is a hereditary disease which is characterized by synchronous or metachronous development of benign (adenoma, hyperplasia) or malignant tumors in the endocrine organs. The presence of medullary thyroid carcinoma and pheochromocytoma are mandatory requirements of MEN 2 syndrome. The purpose of our study was to perform timely diagnosis and optimal surgical treatment of patients with MEN 2 syndrome. Over the past 10 years (1999-2009 years) in the clinic of Surgical Department №1, we have diagnosed the syndrome of MEN type 2 in 5 patients, of whom two women were sisters. In all cases we observed medullary thyroid carcinoma and pheochromocytoma. Two patients had bilateral pheochromocytoma, and the clinical course was characterized with mild arterial hypertension. Primary hyperparathyroidism was observed in 2 patients. Conclusion: in the near relatives of patients with syndrome of MEN 2, you must measure calcitonin, catecholamines, calcium, conduct ultrasound examination of the neck and retroperitoneal space for diagnosis of MEN syndrome.